The Effect of Nutrition Counseling on Complementary Feeding Practice of Mothers Having Infant Aged 6-12 Month - Yulia Arifin; Masrul Masrul; Hirowati Ali (Universitas Andalas, 2019)
Nutrition plays an important role in the human life cycle. Nutrition surveillance in the form of Nutritional Status Monitoring in 2016 showed that 38.9% of children under five in Indonesia experienced nutritional problems. One of the efforts to improve the health and nutrition status of the baby is by improving the knowledge and attitude of the mother in giving complimentary food. This study aim is to know the effect of nutrition counseling on feeding practice of mothers having infant aged 6-12 month in pakan rabaa public health center area solok selatan district in 2018.The design of the study was quasi-experimental with the design of the control group pretest-posttest. The sample of this study was 46 experiment group and 46 control group. Sampling was done by Purposive Sampling technique. Data analysis using the chi-square testThe results of the study were the absence of nutritional counseling on knowledge of mothers with p-value 0.361, there was an effect of nutritional counseling on changes in maternal attitudes with p-value of 0,000 and there was also the effect of nutritional counseling on complementary feeding practice with p-value 0.004.The presence of the influence of nutritional counseling on attitudes and practices of complementary feeding. Health workers are expected to be able to spend time giving counseling about complementary feeding practice regularly so that the goal of counseling at the public health center can be achieved.